PERCEIVED IMPACT OF ONLINE RESOURCES ON THE ECONOMIC LITERACY LEVEL OF ECONOMICS STUDENTS IN FEDERAL UNIVERSITIES IN SOUTH EAST, NIGERIA - OKAFOR, IKECHUKWU GIVESON; OKOYE, OZIOMA MARYJANE; ENEOGU, NJIDEKA DORATHY; EZEUGWU, CHINENYENWA JULIET (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This paper investigated perceived impact of online resources on the economic literacy level of Economics students in Federal Universities in South East Nigeria. Descriptive survey design was adopted. The instrument of data collection was a questionnaire which was developed based on the three (3) research questions. The respondents to the instrument were a selected sample of one hundred and fifty-two students. The method of data analysis was mean and standard deviation while t-test was used to test the hypothesis at 0.05 level of significance. The findings revealed that online resources encourage learning of current economic matters outside the classroom. Also, E-resources like blogs keep students updated on latest news about the country’s economy, and economic conditions of other nations with which they can make valid generalizations. This study has significant implications for policy, highlighting the crucial role of online resources in enhancing economic literacy among Economics students in federal universities. The findings highlight the importance of investing in digital infrastructure, including internet facilities, to support online learning. Furthermore, the study emphasizes the need for digital literacy programs that teach students how to effectively navigate online resources and develop critical thinking skills